Hemodynamic evaluation with turbo brisk - a rapid phase contrast angiography technique - Kortright, Eduardo; Doyle, Mark W.; Anayiotos, Andreas (My University, 2000)
Hemodynamic imaging by phase contrast angiography was significantly accelerated by selective interpolation and segmentation in k-space using TURBO BRISK. The method was tested in vitro on three independent flow fields, representative of human blood rheology: a straight tube simulating the descending aorta, a curved tube simulating the aortic arch and a two-chamber orifice flow model simulating valvular regurgitation. The results were compared to data obtained by Laser Doppler Velocimetry (LDV) and showed good agreement. For the straight tube, the flow velocity obtained by five TURBO BRISK methods with increasing segmentation factors and corresponding time savings showed good agreement with LDV. For the curved tube, the velocity showed good general agreement with some differences in the decelerating part of the cycle, and in the low-velocity secondary flow structures. The orifice flow evaluation, the most time consuming case, was performed by the control volume method. It showed good agreement with actual flows through the orifice. Data acquisitions for TURBO-4 BRISK could be performed in 20s for each velocity component. The method shows promise for breath-hold acquisitions in clinical applications, including calculation of blood flow volumes through diseased arteries, measurement of blood backflow volumes through dysfunctional heart valves to time valve replacement operations, and evaluation of arterial wall shear stress, an important factor in the genesis of atherosclerosis.
Keywords: Atherosclerosis; Hemodynamics; Blood--Rheology; Signal processing; Lactate dehydrogenase virus